The state of the arts in Ghana – a critical appraisal of Organization and Administration - Doku, Mark Anthony (2012)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Arts in Art Education.